Effect of enriched rice washing on selenium content - Silva-Trejos, Paulina (2013)
Rice is a common food in the diet of Costa Ricans.  Currently about 45% of the rice consumed is produced locally and the rest is imported from the United States and Argentina. In Costa Rica, prostate cancer is the most frequent tumor diagnosed in men, and investigations support the antioxidant effect of selenium in the prevention of prostate cancer.  Rice consumption in Costa Rica is estimated at 130 g for feeding time per person. The Ministry of Health, the lead agency in public health, considering that rice is consumed in the three meals, decreed in 2006 the enrichment of domestic and imported rice with 107 mg / kg of selenium. It is customary to wash the rice before cooking it, without following the recommendations included in the product package.  In this investigation we determined the effect of washing on the selenium content and found that it decreases between 51% and 79% for the different types of rice, with a standard washing procedure.  The technique used for measurement of selenium was atomic absorption spectroscopy with hydride generation, and digestion of the samples was performed with nitric acid in a microwave oven.